Pembuatan Aplikasi Simulasi Ujian Praktik Pengambilan Surat Izin Mengemudi Kendaraan Roda Empat - Yohan Kurniadi; Liliana Liliana; Kristo Radion Purba (Jurnal Infra, 2016)
The development of video games today have been growing rapidly. The latest technology, allows users to feel like in the virtual world of a video game. Simulation Game is one genre that can teach something to the user. Simulation Games like driving simulator can be used as a training tool before encountering a real condition with real vehicles.This thesis will generate a 3-dimensional application that can simulate practice exams for four-wheeled vehicles. The development of the application is using Unity Engine program with C# programming language. Logitech G27 Steering Wheel is used as the controller.The test results showed that the steering wheel device can generate output in accordance with steering control on the car. In this thesis, the test results indicate that the materials of practice test are made in 3-dimensional view is look alike reality with the practice of the real exam. This application also can be done by using the device steering wheel to steer the car in a virtual world.